Harmonisasi Kemanfaatan dan Keadilan dalam Perlindungan Hukum Bagi Konsumen - Hawa, Rianti; Supratman, Rudi; Palupi, Retno (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2023)
Consumer is everyone who uses goods and / or services available in society, either for their own interests, as well as for family and other people and other living things and not for trade. In practice, of course, business actors are responsible for the goods and services consumed by consumers, and if the goods and services are in accordance with the agreement, it will provide benefits for consumers, but if it turns out that the goods or services purchased do not provide the results desired by consumers, such as experiencing damage, hidden defects, consumers have the right to ask for compensation to business actors, and given in accordance with consumer rights based on the principle of justice so that legal consumer protection can be fulfilled. The purpose of this study is to find out how harmonization of the principles of benefit and justice in providing legal protection for consumers, including in fulfilling fair compensation in resolving consumer disputes with business actors, so that in line with the principles of benefits and justice can provide legal protection for consumers and responsibilities to business actors in accordance with their respective rights and obligations.